Quantitative Trait Locus Analysis and Identification of Candidate Genes for Micronaire in an Interspecific Backcross Inbred Line Population of Gossypium hirsutum × Gossypium barbadense - Pei, Wenfeng; Song, Jikun; Wang, Wenkui; Ma, Jianjiang; Jia, Bing; Wu, Luyao; Wu, Man; Chen, Quanjia; Qin, Qin; Zhu, Haiyong; Hu, Chengcheng; Lei, Hai; et al. (Frontiers in Plant Science, 2021)
Cotton is the most important global cash crop and provides indispensable natural fibers for the textile industry. Micronaire (MIC) is determined by fiber fineness and maturity and is an important component of fiber quality. Sea-island, Egyptian, or Pima cotton (Gossypium barbadense L.) possesses long, strong and fine fibers, while upland cotton (Gossypium hirsutum L.) is high yielding and widely cultivated worldwide. To identify quantitative trait loci (QTLs) and candidate genes associated with MIC, an interspecific backcross inbred line (BIL) population of 250 lines, developed from upland cotton CRI36 and Egyptian cotton Hai7124, was evaluated in 9 replicated field tests. Based on a high-density genetic map with 7709 genotyping-by-sequencing (GBS)-based single-nucleotide polymorphism (SNP) markers, 25 MIC QTLs were identified, including 12 previously described QTLs and 13 novel QTLs. Importantly, two stable MIC QTLs (qMIC-D03-2 on D03 and qMIC-D08-1 on D08) were identified. Of a total of 338 genes identified within the two QTL regions, eight candidate genes with significantly different expression between TM-1 and Hai7124 were identified. Our research provides valuable information for improving MIC in cotton breeding.